Minimalist security and privacy schemes based on enhanced AES for integrated WISP sensor networks. (1st January 2013) - Kong, Jia Hao; Ang, Li-Minn; Seng, Kah Phooi
Extensive development has yielded the improved version of the radio frequency identification (RFID) called the wireless identification sensing platform (WISP). Recent research suggests the combined system of integrated RFID and wireless sensor network (WSN) used for coupling the virtual and physical world, bridging the gap between WSN and RFID. The possibility of having an integrated WISP sensor network might be a starting point for the new future smart system's application. And yet, in every system there will be sensitive data that requires various degree of data encryption. Given the steep design challenge and the limited resources provided on both WSN and WISP's platforms, we can foresee that the design trend has to be memory and hardware efficient. In this paper, we present a minimalist approach to securely encrypt, authenticate and exchange secret keys with a minimal instruction set computer (MISC) processor based on the AES algorithm, termed the enhanced AES (NAES) processor.